2022
DOI: 10.5650/jos.ess22031
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Study on the Constituents of <i>Angelica sinensis</i> (Oliv.) Diels, <i>Angelica dahurica</i> (Hoffm.) Benth. & Hook.f. ex Franch. & Sav., <i>Angelica pubescence</i> Maxim and <i>Foeniculum vulgare</i> Mill. Essential Oils

Abstract: tion of human body 3) . With the development of modern medicine, the mechanism of partial inflammation has been preliminarily speculated 4) . It seriously affected people s normal life because of its characteristics of strong suddenness, long duration and repeated attacks 5) . While synthetic drugs are available to fight inflammation effectively, the Abstract: Umbelliferae plants, which are widely used as traditional Chinese medicine because of their characteristics of relieving rheumatism, alleviating fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nevertheless, several cellular studies have reported the capability of other EOs in alleviating inflammation [ 19 , 20 , 56 , 65 , 75 ], but to the best of our knowledge, this is the first report demonstrating the anti-inflammatory role of AEO and LEO in a GDM-HUVEC in vitro model.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, several cellular studies have reported the capability of other EOs in alleviating inflammation [ 19 , 20 , 56 , 65 , 75 ], but to the best of our knowledge, this is the first report demonstrating the anti-inflammatory role of AEO and LEO in a GDM-HUVEC in vitro model.…”
Section: Discussionmentioning
confidence: 95%
“…Much evidence from in vitro and animal studies proves that EOs have multiple biological activities, such as anticancer [ 4 , 5 ], antiviral [ 6 , 7 , 8 , 9 ], antibacterial [ 10 , 11 , 12 , 13 ], antifungal [ 14 , 15 ], antibiofilm [ 16 , 17 , 18 ], anti-inflammatory [ 19 , 20 , 21 ], and antioxidant [ 19 , 22 , 23 , 24 , 25 ] effects, which constitute the starting point for the in vivo assessment of those properties in various therapeutic and cosmetic fields [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Nevertheless, since great consideration has been given to the effective use of EOs in clinical procedures, further systematic animal studies and clinical investigations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The volatile oils of A. dahurica roots showed bioactivities such as anti-inflammation [ 13 , 14 ] and antioxidation [ 15 , 16 ]. According to literatures, the volatile oil extracted from the root of A. dahurica were mainly alkenes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radix Angelica Sinensis and Chuanxiong Rhizoma as major herbal ingredients of the FSS formula possessed blood nourishment, wind elimination, and pain alleviation in TCM perspectives ( Huang et al, 2020 ). Furthermore, modern medical studies reported that these two Chinese medicines had anti-nociceptive and anti-inflammatory activities ( Wang et al, 2020 ; Li C. et al, 2022 ). Tetramethylpyrazine (ligustrazine) from Chuanxiong Rhizoma showed an anti-inflammatory effect on cells by regulating related signaling pathways such as nuclear factor kappa-B (NF-κB) and PI3K/AKT ( Zheng et al, 2013 ; Zhang et al, 2020 ; Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%